2020
DOI: 10.1002/admi.201901933
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Effect of Surface Modification of Microporous Carbon by Phosphorus/Oxygen as well as the Redox Additive of p‐Aminophenol for High‐Performance Supercapacitors

Abstract: In present work, commercial microporous carbon materials are modified on the surface with phosphorus/oxygen species by using phytic acid as sole dopant, which plays crucial effect on the carbon structure, wettability, electrical conductivity, and capacitive behaviors. It reveals that with increasing the content of heteroatoms, the porosity and contact angle are decreased but the conductivity turns much larger. Furthermore, p‐aminophenol is introduced to serve as redox additive, which can produce more active su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The results indicated that the control samples contained abundant micropores. [ 42 ] However, it was worth noting that the N/O‐PCs showed type‐Ι and IV isotherm characteristics, and had H 4 ‐type curve with obvious hysteresis loop, reflecting that a large number of micropores and mesopores were formed. [ 43 ] The pore size distribution characteristics of all the samples were displayed in Figure 3b, the pore sizes of the N/O‐PCs were mainly centered at 1.3 nm belonging to micropores and there were rich mesopores in the range of 3.5–4.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the control samples contained abundant micropores. [ 42 ] However, it was worth noting that the N/O‐PCs showed type‐Ι and IV isotherm characteristics, and had H 4 ‐type curve with obvious hysteresis loop, reflecting that a large number of micropores and mesopores were formed. [ 43 ] The pore size distribution characteristics of all the samples were displayed in Figure 3b, the pore sizes of the N/O‐PCs were mainly centered at 1.3 nm belonging to micropores and there were rich mesopores in the range of 3.5–4.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental data for training our ML models were collected from the literature, and the formulas for obtaining the processed data are introduced in Table S2. , While there have been numerous investigations on the capacitance of heteroatom-doped carbons in aqueous electrolytes, only a limited number have provided the detailed structure parameters and the surface chemical composition. The capacitance data employed in this study were acquired through measurements conducted in three-electrode cell configurations, all within the same potential window range of 1 V. The three-electrode measurements provide more precise control over potential and current than two-electrode measurements.…”
Section: Models and Methodsmentioning
confidence: 99%
“…1,2 Presently, aqueous supercapacitors (ASCs) are attracting signicant attention among the various energy storage devices owing to their low pollution, intrinsic safety, rapid charge/discharge rates, high power density, and long cycle stability. [3][4][5] Despite these advantanges, the low energy densities of ASCs hinder their large-scale production owing to their water decomposition voltage limit (∼1.23 V), which reduces the operating voltage window and inhibits ion adsorption on the surface of the activated carbon-based electrode. [6][7][8][9] Therefore, it is essential to develop high energy density devices.…”
Section: Introductionmentioning
confidence: 99%